Analisa Unjuk Kerja Motor Bensin Akibat Pemakaian Biogasoline - Wiratmaja, I Gede (Jurnal Energi Dan Manufaktur, 2012)
Renewable energy has become a major issue and debate in recent years. This is not apart from the depletion of energyreserves do not renewable in the bowels of the earth. Particularly oil, which is estimated to 20 years from now will be exhaustedso that the solution should be found to obtain adequate alternative energy. One way is to use what is biogasoline alternative fuelmixture of gasoline and alcohol with a specific ratio, it is due to biofuels (alcohol) can not stand alone as a pure substitute forconventional fuels, especially gasoline. This Biogasoline tested on a conventional engine to find work and performance comparedwith performance with the use of gasoline enginesIn a study conducted to find out is by direct testing methods in the field. Testing is done by comparing the variation of theratio of gasoline and alcohol mixture with varying spin machine, using a tool called the Universal dynamometer Module .Results from research conducted by the above method obtained the following results: Biogasoline (90:10) to producepower and greater torque compared to other fuels tested in this study, but still more wasteful in terms of fuel consumption.
Keywords: Biogasoline, dynamometer, performance